2009
DOI: 10.1007/s11224-008-9403-y
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic interactions in metal halide molecules

Abstract: Electron-vibrational (usually called ''vibronic'') interactions in molecular systems with electronically degenerate, or near degenerate states produce a variety of novel properties best known as the Jahn-Teller effect, or the related Renner-Teller and pseudo-Jahn-Teller effects. These effects have been observed and described for decades by different experimental methods; however, the real renaissance in this field happened due to the ever increasing potentials of quantum chemical calculations that can reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Following closely Ref. [26], we observe that local change in the electron density distribution will generate an imbalance with respect to the corresponding density of the positive background. As a result, there will be a restoring force that will tend to compensate this density imbalance.…”
Section: A Basic Set-up Of Physical Model and The Main Featuressupporting
confidence: 74%
“…Following closely Ref. [26], we observe that local change in the electron density distribution will generate an imbalance with respect to the corresponding density of the positive background. As a result, there will be a restoring force that will tend to compensate this density imbalance.…”
Section: A Basic Set-up Of Physical Model and The Main Featuressupporting
confidence: 74%
“…However, symmetry lowering due to vibronic interactions can be observed for linear molecules as well, and that is the Renner-Teller effect. This effect is weaker than the Jahn-Teller effect, it usually has a dynamic character, and is difficult to detect by experimental means [23,29]. The computations of chromium difluoride showed that the ground state of the molecule is bent or quasi-linear due to a Renner-Teller distortion.…”
Section: Renner-teller Effectmentioning
confidence: 98%
“…The Jahn-Teller effect is one of the electron-vibrational (often called ''vibronic'') interactions in molecular systems that are in degenerate electronic states [23].…”
Section: Jahn-teller Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps in his earlier discussions with Landau, Teller did not take into account the possibility that the quadratic terms might also cause distortion and Landau might have thought of this possibility but did not elaborate on it [11]. It is also possible that Landau made a mistake as the story implies-but, again, as Teller himself told us, ''it bothered me that he was usually not wrong, so maybe he was always right with the exception of linear molecules [8,9].''…”
mentioning
confidence: 99%